Guarantee of the social rights of children with chronic conditions: reinventing care towards civil rights - Tatiana Silva Tavares; Kênia Lara Silva; Regina Garcia de Lima; Elysângela Dittz Duarte (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the experiences of families in the exercise of the rights of children with chronic conditions in public health, education and social assistance institutions. Method: ethnographic multiple case study, with qualitative approach, following the theoretical approach of Boaventura Santos. Experiences of the families of these children in a city were studied through interviews with family members, managers and professionals from social institutions (35), participant observations in social spaces (13) and creation of eco-maps (3). Critical Discourse Analysis was performed. Results: the offer of services is lower than the demand, and exclusion processes persist. Given the hegemony of neoliberal and normality ideologies, meetings between family members and professionals revealed obstacles to civil rights; however, when these ideologies were challenged, the realization of their rights was enhanced. Final considerations: the care to promote civil rights requires family members, managers and professionals to develop subjectivities that overcome neoliberal and normality ideologies, recognizing these children as subjects of law.